Intersection Between Large Granular Lymphocyte Leukemia and Rheumatoid Arthritis - Moosic, Katharine B.; Ananth, Kusuma; Andrade, Felipe; Feith, David J.; Darrah, Erika; Loughran, Thomas P. (Frontiers in Oncology, 2022)
Large granular lymphocyte (LGL) leukemia, a rare hematologic malignancy, has long been associated with rheumatoid arthritis (RA) and the diseases share numerous common features. This review aims to outline the parallels and comparisons between the diseases as well as discuss the potential mechanisms for the relationship between LGL leukemia and RA. RA alone and in conjunction with LGL leukemia exhibits cytotoxic T-cell (CTL) expansions, HLA-DR4 enrichment, RA-associated autoantibodies, female bias, and unknown antigen specificity of associated T-cell expansions. Three possible mechanistic links between the pathogenesis of LGL leukemia and RA have been proposed, including LGL leukemia a) as a result of longstanding RA, b) as a consequence of RA treatment, or c) as a driver of RA. Several lines of evidence point towards LGL as a driver of RA. CTL involvement in RA pathogenesis is evidenced by citrullination and granzyme B cleavage that modifies the repertoire of self-protein antigens in target cells, particularly neutrophils, killed by the CTLs. Further investigations of the relationship between LGL leukemia and RA are warranted to better understand causal pathways and target antigens in order to improve the mechanistic understanding and to devise targeted therapeutic approaches for both disorders.